Role of mucosal high‐risk human papillomavirus types in head and neck cancers in central India. Issue 1 (19th April 2017) - Gheit, Tarik; Anantharaman, Devasena; Holzinger, Dana; Alemany, Laia; Tous, Sara; Lucas, Eric; Prabhu, Priya Ramesh; Pawlita, Michael; Ridder, Ruediger; Rehm, Susanne; Bogers, Johannes; Maffini, Fausto; et al.
Abstract : Mucosal high‐risk (HR) human papillomaviruses (HPV) cause a subset of head and neck cancers (HNC). The HPV‐attributable fraction of HNC varies substantially between countries. Although HNC has a very high incidence in the Indian subcontinent, information on the contribution of HPV infection is limited. Here, we evaluated the HPV‐attributable fraction in HNC ( N  = 364) collected in a central region of India. HNC from three different anatomical subsites were included, namely, oral cavity ( n  = 252), oropharynx ( n  = 53) and hypopharynx/larynx ( n  = 59). In this retrospective study, HPV‐driven HNC were defined by presence of both viral DNA and RNA. Overexpression of p16 INK4a was also evaluated. HR‐HPV DNA was detected in 13.7% of the cases; however, only 2.7% were positive for both HPV DNA and RNA. The highest percentage of HPV DNA/RNA double positivity was found in oropharynx (9.4%), followed by larynx (1.7%) and oral cavity (1.6%) ( p  = 0.02). More than half of HPV DNA/RNA‐positive cases were p16 INK4a ‐negative, while a considerable number of HPV RNA‐negative cases were p16 INK4a ‐positive (17.9%). HPV16 was the major type associated with HNC (60.0%), although cases positive for HPV18, 35 and 56 were also detected. Our data indicate that the proportion and types of mucosal HR‐HPV associated with HNC in this central Indian region differ from those in other (developed) parts of the world. This may be explained by differences in smoking and/or sexual behaviour compared with North America and northern Europe. Moreover, we show that p16 INK4a staining appeared not to be a good surrogate marker of HPV transformation in the Indian HNC cases. Abstract : What's new? Infection with human papillomavirus (HPV) is responsible for a subset of head and neck cancers, but its contribution to this prevalent cancer in India remains unknown. In a large retrospective study, the authors used sensitive assays for the detection of HPV DNA and RNA, and compared their positivity with that of p16 INK4a, a surrogate marker of HPV infection. They find that the HPV contribution to HNC in central India is lower than in many developed parts of the world, pointing to regional differences in the association of HPV and head and neck cancers that require further investigation.